The Numerical Comparison Study On The Effect Of The Anti-Icing Methods On Thermal Stress Distribution Of Nacelle Lip-Skin - Muhamad Yusli, Siti Rosyada (Universiti Sains Malaysia, 2018)
In-flight ice accumulation is a serious hazard. It ruins the smoothness flow of air, increasing drag, degrading control authority and decreasing the ability of an airfoil to lift. The worst situation would be when broken ice particles are absorbed, which ingestion of would break down the engine. This situation shows that anti-icing methods are very important to overcome this problem. Therefore, the main objective of this project is to study the effect of the anti-icing methods on thermal stress distribution of nacelle lip-skin. There are two anti-icing methods that will be compared in this project, which are Swirling Anti-Icing (SAI) and Piccolo Tube Anti-Icing (PTAI) methods. Computational Fluid Dynamics (CFD) has been widely used to study the effect of ice accretion onto the nacelle lip skin. CFD analysis can help to save time and effort, as well lower the cost by reducing the number of experiments required during the development. In order to achieve the main objective, the fluid structure interaction (FSI) is utilized. ANSYS Fluid Flow (FLUENT) is used in this project to study the thermal distribution and it will be paired with static structural to investigate any mechanical deformation. Simulation results shows that the SAI is a better anti-icing system compared to PTAI as the maximum stress value is lower than PTAI. Aluminium 2 series is chosen as the best material because it has the lowest value of the maximum strain.